Timber harvesting and conservation status of forest species in the Ecuadorian Amazon - López-Tobar, Rolando; Herrera-Feijoo, Robinson J.; García-Robredo, Fernando; Mateo, Rubén G.; Torres, Bolier (Frontiers in Forests and Global Change, 2024)
This study focuses on the Ecuadorian Amazon, a crucial region for forest biodiversity and conservation of native species, which faces challenges due to timber extraction. The research objective was to characterize timber harvesting during 2012 to 2021, focusing on the ten most harvested forest species in terms of volume and provincial distribution, as well as their conservation status according to the IUCN. For the methodology, data were extracted and analyzed from Ecuador’s Forest Management System (SAF), focusing on timber extraction in six provinces and assessing 210 species. The results revealed that, from 2,627,659.17 m3 authorized, 2,296,238.08 m3 were harvested, representing 54.17% of the national timber harvest from native forests. Species of the Fabaceae family predominated in number and volume, with yields varying from 0.5 m3/ha in Orellana to 2.8 m3/ha in Zamora Chinchipe. Analysis of the IUCN categories showed that 67.6% (142 species) are Least Concern (LC), while 3.3% (7 species) are Vulnerable (VU), and 1% (2 species) Endangered (EN). Two species were listed as Data Deficient (DD), one as Critically Endangered (CR) and one as Near Threatened (NT). It is crucial to note that, of the 210 species analyzed, 55 species (26.2%) are not included in the IUCN database, highlighting the importance of more detailed assessments for their conservation and distribution.